PELATIHAN EKONOMI KREATIF UNTUK PEMUDA PADA MASA KKN-DR DI KELURAHAN NGAMPEL MOJOROTO KOTA KEDIRI - Nurul Farida; Ahmad Badi' (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
The purpose of this activity is to encourage the youth economy and market it on social media. youths are trained to make beads, paintings, and calligraphy to be further marketed through social media. This community service activity uses the ABCD or Asset Based Community Development (ABCD) approach which prioritizes the utilization of assets and potential in the community. ABCD stages include: Discovery, Dream, Design, Define, and Destiny. KKN-DR conducted in the Ngampel Village, Mojoroto District, Kediri City with a focus on creative economy training targeting hard and soft skills. Where are the hard skills on the ability to make beads, paint, and calligraphy. Meanwhile, soft skills aim at mastering online-based technology to market the products that have been made. The making of beads, painting, and calligraphy did not encounter significant obstacles, bearing in mind that there are many materials for making beads in the Ngampel Mojoroto area. In product marketing through social media and marketplaces, it takes observation and experience to understand promotional language and also compare existing product prices.